1978
DOI: 10.1063/1.325397
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-orientation dependence of the epitaxial regrowth rate from Si-implanted amorphous Si

Abstract: Amorphous layers, approximately 4000 Å thick, were formed on single-crystal Si samples by implantation of 28Si ions at LN2 substrate temperature. Channeling-effect measurements with MeV 4He ions were used to measure the thickness of the amorphous layers and to measure the subsequent epitaxial regrowth on the underlying crystalline substrates. For annealing temperatures between 450 and 575 °C, the growth rate showed a strong dependence on the substrate orientation with 〈100〉-oriented samples exhibiting about a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(148 citation statements)
references
References 12 publications
11
136
1
Order By: Relevance
“…This effect is enhanced in the case of a planar amorphous-crystal interface. It shows even higher activation energy for recrystallization, 2.44 eV, in very good agreement with the value measured in the experiments, 2.7 eV [16]. In the limit, as already stated, a pure amorphous matrix would be described by bond defects completely surrounded by other bond defects.…”
Section: Atomistic Model For Si Amorphization and Recrystallizationsupporting
confidence: 77%
“…This effect is enhanced in the case of a planar amorphous-crystal interface. It shows even higher activation energy for recrystallization, 2.44 eV, in very good agreement with the value measured in the experiments, 2.7 eV [16]. In the limit, as already stated, a pure amorphous matrix would be described by bond defects completely surrounded by other bond defects.…”
Section: Atomistic Model For Si Amorphization and Recrystallizationsupporting
confidence: 77%
“…18 In particular, Drosd and Washburn 19 formulated that the main criterion for Si in the amorphous phase to crystallize is the formation of at least two undistorted bonds with the crystal. On the basis of geometrical considerations, it can be concluded that this requirement is easily met in the (100) plane because one incoming Si atom can establish the necessary bonds.…”
Section: Growth On Nonpatterned Substratesmentioning
confidence: 99%
“…During annealing at 800°C for 30 min, the amorphous layer recrystallizes but leads to the formation of a polycrystalline layer containing a high density of extended defects. Usually, annealing of an ion-beam induced amorphous layer occurs by layer-by-layer solid phase epitaxial growth 49 ͑SPEG͒ and results in a low defect density in the recrystallized volume. When the amorphous layer extends to the surface, the defects forming at the amorphous/crystalline ͑a / c͒ interface are swept at the same time that the recrystallization advances up to the surface, leaving defects only behind the initial a / c interface.…”
Section: A Amorphization-recrystallizationmentioning
confidence: 99%